2017
DOI: 10.3390/rs9100979
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Aerosol Optical Depth Using an Airborne Polarimeter over North China

Abstract: Abstract:The airborne Atmosphere Multi-angle Polarization Radiometer (AMPR) was employed to perform airborne measurements over North China between 2012 and 2016. Seven flights and synchronous ground-based observations were acquired. These data were used to test the sensor's measurements and associated aerosol retrieval algorithm. According to the AMPR measurements, a successive surface-atmosphere decoupling based algorithm was developed to retrieve the aerosol optical depth (AOD). It works via an iteration met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Our transfer characteristics obtained here are the best for monolayer 2H‐MoTe 2 FETs, and also comparable to the best results for few‐layer 2H‐MoTe 2 FETs made on CVD‐grown or exfoliated flakes (Table S1, Supporting Information). It also compares very well with those of single‐crystal‐like MoS 2 FETs with wafer‐scale monolayer channel . The mobilities calculated from 100 devices fall in a narrow range of 19.2–27.0 cm 2 V −1 s −1 , suggesting the relative high‐quality uniformity of our MBE‐derived wafer‐scale monolayer 2H‐MoTe 2 film (Figure h).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Our transfer characteristics obtained here are the best for monolayer 2H‐MoTe 2 FETs, and also comparable to the best results for few‐layer 2H‐MoTe 2 FETs made on CVD‐grown or exfoliated flakes (Table S1, Supporting Information). It also compares very well with those of single‐crystal‐like MoS 2 FETs with wafer‐scale monolayer channel . The mobilities calculated from 100 devices fall in a narrow range of 19.2–27.0 cm 2 V −1 s −1 , suggesting the relative high‐quality uniformity of our MBE‐derived wafer‐scale monolayer 2H‐MoTe 2 film (Figure h).…”
supporting
confidence: 69%
“…monolayer WS 2 on Au foils and 6 in. monolayer MoS 2 on soda‐lime glasses were demonstrated . By controlling the kinetic rates of nucleation and crystal growth, a centimeter‐scale few‐layer 2H‐MoTe 2 film with domain size up to ≈300 µm was synthesized in 2D limit .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [33] revealed the spatial and temporal characteristics of AOD values during 1980-2008 over mainland China using the TOMS AOD and MODIS AOD products (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). Meanwhile, many studies on the spatial and temporal variations of AOD values in regional scale in Chinawere conducted using meteorological measurement and satellite signals [10,26,[34][35][36][37][38][39][40]. However, few studies have been made for analyzing the characteristics and driving factors of AOD values in different climate zones and terrain features over mainland China, due to the relative sparse AOD and meteorological measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral sensitivities of the polarized reflectances obtained from research scanning polarimeter and micropolarimeter measurements over vegetated surfaces were studied previously Waquet, Léon, et al, 2009), and the offsets of the regression lines were determined as small with slopes close to 1. This conclusion has been applied to aerosol retrieval for a number of airborne polarimetric instruments, such as the research scanning polarimeter and the advanced multi-angle polarization radiometer (Qie et al, 2015;Wang et al, 2014Wang et al, , 2017). This conclusion has been applied to aerosol retrieval for a number of airborne polarimetric instruments, such as the research scanning polarimeter and the advanced multi-angle polarization radiometer (Qie et al, 2015;Wang et al, 2014Wang et al, , 2017).…”
Section: Introductionmentioning
confidence: 99%